(untitled) (REMUNOM, 2024)
ABSTRACT This article aims to discuss the possible liability of digital influencers, presenting a conclusion on how the matter should be resolved in practice considering the rules contained in the Civil Code, Consumer Protection Code and CONAR. To develop the research, the research method was used: bibliographic and documentary, through a careful study of legislation and jurisprudence. The topic is current and has outstanding relevance, since the digital influencer is present on digital platforms, as well as social networks and has great reach due to instant information, while they share their daily routines, in which they make your followers purchase the products presented there. Therefore, how will the legislation apply to consumers who purchased products or services from the digital influencer through advertising? What is the relevance of digital influencers in consumer decision-making? The conclusion reached is that the digital influencer will be able to respond in an objective and supportive way with the company, as he precisely conveys and mediates the company and consumer relationship, whether through publications with videos, photos, testimonials, on their profiles in which this automatically links to the company. It is precisely because of this connection that this media professional has this objective and joint responsibility in the event of legal action, together with the company, and such liability may occur due to a product that was not delivered or a failure to provide a service.